2011
DOI: 10.1002/rcm.5124
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of collision‐induced dissociation energy on molecular degrees of freedom as a means to assess relative binding affinity in multivalent complexes

Abstract: In collision-induced dissociation mass spectrometry experiments, the collision energy required for dissociation linearly depends on the degrees of freedom in the precursor ion. The magnitude of the slope of this relationship previously has been shown to qualitatively correlate to the relative binding strength of a noncovalently bound, monovalent complex. The goal of the work presented here is to determine if a similar methodology can be applied for assessing relative binding strengths in multivalent species. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Comparison of NCE values, although qualitative, has been used to infer the stability of other complexes. 46 As expected, it was observed that the complexes fragment at a much lower NCE value than the ion of the initial hexaaryl [3]radialene owing to the weaker noncovalent forces involved.…”
Section: ■ Results and Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Comparison of NCE values, although qualitative, has been used to infer the stability of other complexes. 46 As expected, it was observed that the complexes fragment at a much lower NCE value than the ion of the initial hexaaryl [3]radialene owing to the weaker noncovalent forces involved.…”
Section: ■ Results and Discussionsupporting
confidence: 59%
“…The stability of the complexes were probed through comparison of the signal intensities for a particular ion with increasing normalized collision energy (NCE) relative to the signal intensities that are observed with an NCE of zero. Comparison of NCE values, although qualitative, has been used to infer the stability of other complexes . As expected, it was observed that the complexes fragment at a much lower NCE value than the ion of the initial hexaaryl[3]radialene owing to the weaker noncovalent forces involved.…”
Section: Resultsmentioning
confidence: 91%
“…Evaluation of identical samples with time-of-flight MS, which does not activate ions during detection (see Supporting Information), yields masses and isotope patterns that agree well with predicted values. In Figure 1b, the precursor ion survival yields are shown as a function of activation voltage normalized by the number of vibrational degrees of freedom [24, 19]. The trends in peptide complex stability are nearly identical to those observed by mass shifting in Figure 1a (a quantitative comparison is shown in the Supporting Information).…”
Section: Resultsmentioning
confidence: 53%